2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Right to Work [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
The Florida Constitution guarantees that "...the right to work shall not be denied or abridged on account of membership or nonmembership in any labor union or labor organization." This is EDIS document FE414, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.